2018
DOI: 10.1029/2018jc013932
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Upwelling of Subsurface Iron Supplies Seasonally Persistent Phytoplankton Blooms Around the Southern Kerguelen Plateau, Southern Ocean

Abstract: Although the supply of iron generally limits phytoplankton productivity in the Southern Ocean, substantial seasonal blooms are observed over and downstream of the Kerguelen plateau in the Indian sector of the Southern Ocean. Surprisingly, of the oceanic blooms, those associated with the deeper southern plateau last much longer (~3 months) than the northern bloom (~1‐month downstream of northern plateau). In this study, iron supply mechanisms around the southern plateau were investigated, obtaining profiles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…The second float (Float ID: 5904683) is located downstream of the Kerguelan Plateau and drifts along the Subantactic Front (SAF; Figures b and S3a). This is a region of vigorous eddy activity, and the presence of the Kerguelan Islands and hydrothermal vents can act as a source of lithogenic/benthic iron here (Ardyna et al, ; Blain et al, ; Bowie et al, ; Gille et al, ; Schallenberg et al, ). This float happened to see a short‐lived period of growth in July, but the onset to apex is from August till the end of December.…”
Section: Resultsmentioning
confidence: 99%
“…The second float (Float ID: 5904683) is located downstream of the Kerguelan Plateau and drifts along the Subantactic Front (SAF; Figures b and S3a). This is a region of vigorous eddy activity, and the presence of the Kerguelan Islands and hydrothermal vents can act as a source of lithogenic/benthic iron here (Ardyna et al, ; Blain et al, ; Bowie et al, ; Gille et al, ; Schallenberg et al, ). This float happened to see a short‐lived period of growth in July, but the onset to apex is from August till the end of December.…”
Section: Resultsmentioning
confidence: 99%
“…Several physical processes including internal waves and increased vertical eddy diffusivity (Blain et al, ), upwelling (de Baar et al, ; Korb & Whitehouse, ; Schallenberg et al, ), or vertical mixing (Lam & Bishop, ; Tagliabue et al, ; Tyrrell et al, ) have been shown to enhance vertical iron supply to surface HNLC waters. The SAW on the plateau are characterized by weak stratification and are prone to deep winter mixing caused by the strong thermal contrasts and winds that are characteristic of the region (Morris et al, ; Neil et al, ; and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Linear regressions revealed a statistically significant positive relationship between δ 13 C and longitude for C. pyramidata, which may relate to the cluster of enriched values overlapping the same region (just north of the sACCf on the Plateau) we measured high abundances of this species, toward the eastern flank of the Plateau. Particulate organic nitrogen (PON) measurements revealed enriched values along this region, indicating nitrate uptake which suggests new production was occurring here (Schallenberg et al, ). However, we also detected a statistically significant negative relationship between δ 13 C and longitude for C. antarctica , whose highest abundances generally overlapped with those of C. pyramidata .…”
Section: Discussionmentioning
confidence: 94%
“…Regions along the transect where abundances were lowest (between 70°E to 80°E) overlapped with the lowest δ 13 C and δ 15 N values measured for all species, combined. Incidentally, this region, which covers the western area of the Plateau, also measured the most 15 N‐depleted in PON, suggesting nitrogen recycling and ammonia uptake (Schallenberg et al, ).…”
Section: Discussionmentioning
confidence: 97%